AB0903 Efficacy of tildrakizumab in etanercept partial or nonresponders. (12th June 2018) - Crowley, J.; Papp, K.A.; Hong, C.-H.; Parno, J.; Mendelsohn, A.M.; Li, Q.; Cichanowitz, N.; La Rosa, C.
Abstract : Background: Etanercept (ETN) is an anti–tumour necrosis factor (TNF) medication that was among the first biologics approved for psoriasis. Additional medications have been developed or are in development for psoriasis, and patients who do not adequately respond to ETN may benefit from these more recent biologics. Objectives: Here we report the efficacy of tildrakizumab (TIL), a humanised anti–IL-23p19 monoclonal antibody, as evaluated in patients with moderate to severe chronic plaque psoriasis who were partial (Psoriasis Area and Severity Index [PASI]≥50–<75) or nonresponders (PASI <50) to ETN and subsequently rerandomized to TIL in the phase 3 reSURFACE 2 trial (NCT01729754 ). Methods: Patients with psoriasis (≥10% body surface area, Physician's Global Assessment [PGA], and PASI ≥12) participated in reSURFACE 2, a 3-part, 52 week, randomised controlled trial. In Part 1 (Weeks 0–12), patients were randomised to subcutaneous TIL 200 mg, TIL 100 mg, or placebo (PBO) administered at Weeks 0 and 4, or ETN 50 mg administered twice weekly. In Part 2 (Weeks 12–28), TIL and ETN patients remained on the same treatment (TIL administered at Week 16; ETN once weekly), whereas PBO patients were rerandomized to TIL 100 or 200 mg. In Part 3 (Weeks 28–52), ETN responders (PASI ≥75) were discontinued, and partial and nonresponders were switched to TIL 200 mg (administered at Weeks 32, 36, and 48). For this post hoc analysis, the proportion of patients (±SD) with PASI response and PGA response (score of 0 [clear] or 1 [minimal] with at least a 2-grade score reduction from baseline) were determined at Week 52. Primary results from the trial have been previously reported. 1 Results: In total, 1090 patients were randomised. Of the 313 patients randomised to ETN, by Week 28 there were 83 partial responders and 39 nonresponders. At Week 52 (after 20 weeks of TIL treatment) for ETN partial responders, 75%±5%, 34%±5%, 15%±4%, and 58%±5% had achieved PASI 75, 90, 100, and PGA response of 0/1, respectively, with TIL 200 mg treatment. At Week 52 for ETN nonresponders, 54%±6%, 31%±5%, 10%±3%, and 56%±5% had achieved PASI 75, 90, 100, and PGA response of 0/1, respectively, with TIL 200 mg treatment. Adverse events were similar in patients switched from ETN to TIL at Week 28, compared with the patients who were maintained on TIL through Week 52. Conclusions: A substantial portion of patients with moderate to severe chronic plaque psoriasis who were partial or nonresponders to ETN may respond after switching to treatment with TIL 200 mg. TIL may be a reasonable option for those who do not achieve adequate response to ETN. Reference: [1] Reich, et al. Lancet. 2017;390(10091):276–288. Acknowledgements: This study was funded by Merck and Co., Inc. Editorial support for abstract submission was provided by Fishawack Communications and funded by Sun Pharmaceutical Industries, Inc. Analyses were presented at the American Academy of Dermatology . Annual Meeting, San Diego, California, USA, 2018 Disclosure of Interest: J. Crowley Grant/research support from: Abbvie, Amgen, Sun Pharma, Lilly, Novartis, Janssen, Regeneron, Sanofi, Merck, Pfizer, Sandoz, MC2 Therapeutics, Verrica, Consultant for: Abbvie, Sun Pharma, Dermira, Lilly, Novartis, Celgene, Speakers bureau: Abbvie, Lilly, Novartis, Regeneron, Sanofi, K. Papp Grant/research support from: AbbVie, Akros, Amgen, Anacor, Boehringer Ingelheim, Celgene, Dermira, Eli Lilly, EMD Serono, Janssen, Kyowa Hakko Kirin, Meiji Seika Pharma, Merck SharpDome, Mitsubishi Pharma, Novartis, Pfizer, UCB, Valeant, Consultant for: AbbVie, Akros, Amgen, Anacor, Boehringer Ingelheim, Celgene, Dermira, Eli Lilly, EMD Serono, Janssen, Kyowa Hakko Kirin, Meiji Seika Pharma, Merck SharpDome, Mitsubishi Pharma, Novartis, Pfizer, UCB, Valeant, Speakers bureau: AbbVie, Amgen, Celgene, Eli Lilly, Janssen, Kyowa Hakko Kirin, Novartis, Pfizer, UCB, Valeant, C.-H. Hong Grant/research support from: Amgen, Abbvie, Eli Lilly, Janssen, Merck, Novartis, GlaxoSmithKline, Celgene, UCB, Consultant for: Amgen, Abbvie, Eli Lilly, Janssen, Novartis, GlaxoSmithKline, Celgene, Sun Pharma, Speakers bureau: Amgen, Abbvie, Eli Lilly, Janssen, Novartis, Celgene, J. Parno Employee of: Sun Pharmaceutical Industries, Inc., A. Mendelsohn Employee of: Sun Pharmaceutical Industries, Inc., Q. Li Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, N. Cichanowitz Shareholder of: Merck and Co., Inc., Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, C. La Rosa Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA